Analysis and Design of Production Monitoring Information Systems on Label Shoe Manufacturing Companies - Jansen Wiratama; Rudi Sutomo; Victor Ilyas Sugara (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2023)
Digital technology can be used to solve problems that arise from business activity. One company that has not optimally used digital technology is PT Tiga Tapak Mutiara, which is engaged in manufacturing shoe labels. In its business process, each related division collects data, and the data collection results will be reported to the manager to unify work activities. The production data collection process has not been carried out optimally by the relevant divisions because the conventional recording is still carried out using a spreadsheet application which can slow down the reporting process to be monitored by the leadership. As a result, a slow process can impact not completing production on time. In addition to the problem of data collection, another problem is that the completion of orders received earlier is not compared to the orders received last. The aim and contribution of this research are to integrate business processes to overcome these problems in data collection, monitoring, and order completion activities. It is necessary to design a web-based monitoring information system with the Rapid Application Development (RAD) method and the application of the First In, First Out (FIFO) method so that the ordering process can run according to the time of order. The result of this research is a web-based information system that is useful for integrating business processes to monitor and optimize production activities to be completed on time. This web-based information system has also passed the functionality test using black box testing and is following the company's needs.